Neoadjuvant chemoimmunotherapy achieved a pathologic complete response in stage IIIA lung adenocarcinoma harboring RET fusion: a case report - Dai, Minqian; Wang, Na; Xia, Qin; Liao, Yongde; Cao, Wei; Fan, Jun; Zhou, Diwei; Wang, Sihua; Nie, Xiu (Frontiers in Immunology, 2024)
Neoadjuvant chemoimmunotherapy has demonstrated significant benefit for resectable nonsmall-cell lung cancer (NSCLC) excluding known EGFR/ALK genetic alterations. Recent evidence has shown that neoadjuvant chemoimmunotherapy could be clinically valuable in resectable localized driver gene-mutant NSCLC, though the data still lack robust support, especially for rare oncogenic mutations. Here, we report a patient with stage IIIA lung adenocarcinoma with a RET fusion gene and high expression of PD-L1 who underwent neoadjuvant chemoimmunotherapy and successfully attained a pathologic complete response. The patient has survived for 12 months with no recurrence or metastases after surgery. Our case suggests that this treatment strategy may be an alternative therapeutic option for resectable RET fusion-positive NSCLC patients.